Spatial autocorrelation study for laser beam quality estimation. (July 2020) - Scifo, Jessica; Dotto, Alessio Del; Ferrario, Massimo; Pompili, Riccardo; Villa, Fabio
Abstract: High brightness electron beam is required by several applications in the accelerator physics field. In order to have a high brightness beam, that means a high current and a low emittance beam, it is important to study, among other things, the beams non uniformity due to the non perfect transverse laser beam uniformity. Regarding the transverse analysis of the beam, statistical tools as mean and standard deviation are usually used. In this work we will show how the autocorrelation function of a photocathode laser can be used for monitoring the spatial distribution of the beam non-uniformity, strictly connected with the high electron beam emittance: we will apply our analysis on the SPARC_LAB data.